Building and measuring e-learning scale from the point of view of students of the College of Physical Education and Sports Sciences - University of Baghdad - Dhuha Hadi; Dr. Widad Kadhum (physical education and sport sciences college for women/ Baghdad University, 2021)
Abstract: The research covered five chapters:       So, the first chapter definition of the research is from the introduction to the research and its importance, as the importance of the research lies in an expression of the reality of e-learning as it is one of the new patterns of the educational process and its role in enhancing communication and interconnectedness between the learners from the students 'point of view Physical Education and Sports Sciences for Girls, University of Baghdad, as for the problem The research was, and through the researcher's acquaintance with many previous studies, references and sources, and being a student at the College of Physical Education and Sports Sciences - University of Baghdad, I noticed that it is worth researching to identify the reality of e-learning and its effective role in enhancing communication and interdependence and suggesting the best ways for development and Standing on the strengths to support them and the weaknesses to address them, and thus this study will be a source of a lot of information regarding e-learning, either the goal of the research was to build a scale for the reality of e-learning and to identify the reality of e-learning and its role in enhancing communication and interconnectedness among the educated in the face of Students considered Physical Education and Sports Sciences - University of Baghdad. As for the imposition of research, there were significant differences of statistical significance between students 'responses in the College of Education. Physical and sport sciences - University of Baghdad, the second semester is from theoretical studies and previous studies, and the third semester is from the research methodology and its field procedures, as the research method and the two researchers used it the descriptive approach in the survey method because it is the most appropriate to the nature of the problem and the achievement of the research objectives. The research is students of the College of Physical Education and Sports Sciences - University of Baghdad and their number (2293) male and female students represent the various academic stages in the college. As for the field research procedures, they lie in the procedures for building the scale and applying it to the building and application sample, while the fourth semester was presented. And analyzing the results and discussing them. As for the fifth chapter, the researcher concluded that the results indicated a good level from the reality of e-learning. The results showed good levels in the fields of e-learning reality, and the presence of significant differences between students 'responses in the e-learning reality scale. In lieu of classroom learning by the Ministry of Higher Education and Scientific Research in the Corona crisis and continuing to use it, conducting studies are not Fascination by using the e-learning reality scale with some tests and measures on different samples.